“Della scienza e dell’arte nell’educazione” di Thomas Henry Huxley: Un modello unitario di cultura tra armonia e verità (TEST Ticontre. Theory Text Translation, 2022)
The unabridged Italian translation of the essay On Science and Art in Relation to Education (1883) by Thomas Henry Huxley is offered here, acknowledging that translation may contribute to the construction of acultural discourse, through the selection of foreign texts which prove to illuminate themes perceived as crucial in the target context [Venuti]. Indeed, this essay proposes an ideal of culture connoted by the coexistence of the various branches of knowledge. The target text is preceded by an introduction, which analyses the essay within the context of the 19th-century debate on education and discusses the translation strategies adopted.